Plant and environmental sensory signals control the expression of hrp genes in Pseudomonas syringae pv. phaseolicola. - Rahme, L G (1992)
The hrp genes of Pseudomonas syringae pv. phaseolicola control the development of primary disease symptoms in bean plants and the elicitation of the hypersensitive response in resistant plants. We examined the expression of the seven operons located in the 22-kb hrp cluster (L. G. Rahme, M. N. Mindrinos, and N. J. Panopoulos, J. Bacteriol. 173:575-586, 1991) in planta and in vitro under different physiological and nutritional conditions by using chromosomally located hrp::inaZ reporter fusions. We show that (i) a plant signal(s) is specifically required for the induction of the seven hrp operons, during both compatible and incompatible interactions; (ii) hrpL and hrpRS are regulated by different mechanisms in planta and in vitro; and (iii) expression of individual hrp loci is differentially affected by pH, osmotic strength, and type of carbon source: hrpAB, hrpC, and hrpD were downregulated similarly by osmolarity, pH, and certain carbon sources; hrpE expression was affected strongly by pH and carbon substrate and slightly by osmolarity; and hrpF was not substantially affected by any of these factors. These findings suggest complex signaling mechanisms taking place during plant-pathogen interactions.